Xanthogranulomatous Pyelonephritis: A Case Report and Literature Review - Orgeness Jasper Mbwambo; Nelton Rodrick Thobias; Alex Mremi; Jasper Saidi Mbwambo; Frank Bright; Bartholomeo Nicholaus Ngowi (Clinical Case Reports)
ABSTRACT Xanthogranulomatous pyelonephritis (XGP) is a rare form of chronic pyelonephritis, often associated with renal calculus and infection Escherichia coli and Proteus mirabilis are the most frequent organisms isolated in individuals with the disease. Its incidence is 1.4 cases per 100,000 population each year. We present a case of a 69‐year‐old woman who presented with abdominal pain, icterus, fever, non‐projectile vomiting, anemia, and recurrent urinary tract infections. A diagnosis of nephrolithiasis was made and the patient was started on empirical antibiotics. An abdominal pelvic CT scan was performed that showed features suggestive of XGP; a nephrectomy was performed, and a tissue biopsy was taken for histopathology and the results confirmed a diagnosis of XGP. XGP diagnosis is extremely challenging due to its ability to mimic other renal pathologies, and a high degree of suspicion is required. Abdominal pelvic ultrasound is helpful in preoperative diagnosis and a biopsy postoperatively is required to confirm XGP diagnosis. Medical management of XGP with antibiotics and nephrectomy is the best treatment option.